MICROVASCULAR DECOMPRESSION FOR TRIGEMINAL NEURALGIA - Khan, Shahbaz Ali; Khan, Baynazir; Khan, Abdul Aziz; Afridi, Ehtisham Ahmed Khan; Mehmood, Shakir; Muhammad, Gul; Hussain, Iqbal; Zadran, Khalid Khan; Bhatti, Sajid Nazir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Trigeminal Neuralgia (TGN) is the most frequently diagnosed type of facial pain. In idiopathic type of TGN it is caused by the neuro-vascular conflict involving trigeminal nerve. Microvascular decompression (MVD) aims at addressing this basic pathology in the idiopathic type of TGN. This study was conducted to determine the outcome and complications of patients with idiopathic TGN undergoing MVD. Methods: In a descriptive case series patients with idiopathic TGN undergoing MVD were included in consecutive manner. Patients were diagnosed on the basis of detailed history and clinical examination. Retromastoid approach with craniectomy was used to access cerebellopontine angle (CP-angle) and microsurgical decompression was done. Patients were followed up for 6 months. Results: A total of 53 patients underwent MVD with mean age of 51.6±4.2 years and male predominance. In majority of cases (58.4%) both Maxillary and Mandibular divisions were involved. Per-operatively superior cerebellar artery (SCA) was causing the neuro-vascular conflict in 33 (62.2%) of the cases, anterior inferior cerebellar artery (AICA) in 6 (11.3%) cases, both CSA and AICA in 3 (5.6%) cases, venous compressions in only 1 (1.8%) patient and thick arachnoid adhesions were seen in 10 (18.9%) patients. Postoperatively, 33 (68%) patients were pain free, in 14 (26.45%) patients pain was significantly improved whereas in 3 (5.6%) patients there was mild improvement in symptoms. Three (5.6%) patients did not improve after the primary surgery. Cerebrospinal fluid (CSF) leak was encountered in 7 (13.2%) patients post-operatively, 4 (7.5%) patients developed wound infection and 1 (1.8%) patient developed aseptic meningitis. Three (5.6%) patients had transient VII nerve palsy while one patient developed permanent VII nerve palsy. Conclusion: MVD is a safe and effective surgical option for treating patients with idiopathic TGN with better surgical outcome and fewer complications.